Dinâmica molecular semi-quântica com aplicação em moléculas diatômicas - Rodrigo Alves Dias (2003)
In this work we study the electronic problem in the adiabatic approximation (Born-Oppenheimer), in which one assumes that the motion of the nucleus much slower than that of the electrons. This approximation, we consider the static nucleus subject to a electronic potential. With the wavefunctions in this approximation, we calculate the average value of original Hamiltonian, so obtaining a classical e®ective Hamiltonian for the nucleus. Then we used Hamilton's equations to obtain the nuclear motion. We resolve this equations numerically to obtain the normal vibrational modes of simple molecules, eg. diatomic molecules, and where possible, compare with experiments.